PENGARUH KONSEP DIRI MENGENAI PANGGILAN ALLAH TERHADAP KINERJA GEMBALA JEMAAT - R. Edi Soerjantoro; Mikha Agus Widiyanto (Sekolah Tinggi Teologi Ekumene Jakarta., 2020)
The pastor of the church plays an important role in advancing the church and pastoral congregation. The orientation of the implementation of the task is not just to carry out the routine tasks of grazing, but to bring the church to realize God's purpose. In this assignment, a good pastor's performance is needed. The shepherd's self-concept related to God's calling in him influences his behavior in carrying out the ministry. This study aims to examine the effect of self-concept regarding God's calling on the performance of pastors. This research method is a correlational survey with research respondents from pastors in one of the Synods in Jakarta. The results showed that there was no influence of self-concept regarding God's calling on the performance of the pastor. Efforts made to improve positive self-concepts do not have an impact on improving the performance of pastors. The performance of pastors tends to be influenced by their abilities related to their ministry and the ministry team that supports them.